Avaliação da eficácia do Programa Nacional de Alimentação Escolar (PNAE) - Santana, Tatiane Menezes (2013)
The present work has as object of study the National Program of School Food (Programa Nacional de Alimentação Escolar – PNAE). Aimed to verify the effectiveness of the PNAE in a municipal elementary school of Aracaju-Sergipe. The research was delimited to the observation of three dimensions: the school actors responsible for the feeding, the quality of meals served and the actions of food and nutrition education. After a bibliographical and documental analysis, followed the case study, to evaluate the operation of the Program in an education institution, through observations, interviews and forms. Noted several discrepancies between the Program proposal and its implementation. It was found, among the main results, that problems in the Program managing hindered its operation in school.